The construction of reflexive-tolerant pragmatism and the turn to post-secular democracy - Barboza Tello, Marco Léon Felipe (2021)
The evolution of pragmatist philosophy within American philosophy is approached in a propaedeutic way in relation to two central questions: the links between pragmatism and religion, and the primacy of democracy over philosophy, from which we seek to explain the shaping of post-secular democracy understood as a reflexive, cooperative and enthusiastic democracy, and also to raise the balance of the democratic experience from the will to believe in the individual and his or her possibilities.